An etiological examination of behavioral intentions to support shark and stingray conservancy: the effects of beliefs in elasmobranchs’ cognitive and affective capacities - Hancock, Gabriella M.; Dudley, Katie D.; Long, Dede; Lowe, Christopher G. (Frontiers in Marine Science, 2023)
Keystone species populations, including shark and ray taxonomic groups, are declining due to numerous threats. A better understanding of how individual belief structures inform pro-conservation behavioral intentions is therefore critical to foster support for their conservation and the greater biodiversity of world ecosystems. This study conducted a survey to establish the general public’s cognitive beliefs about the mental and affective capacities of two species groups (sharks and stingrays) known to cause injury to humans, and their effects on different behavioral intentions to support their conservation. Results revealed that a range of different behavioral intentions to support animal conservation are driven by a complex interplay of cognitive beliefs, and some effects were specific to a particular species group while others were not. Beliefs in animals’ cognitive awareness and their emotional abilities were predictive of individuals’ self-reported desire to learn more about the animals and their conservation. Beliefs in animals’ cognitive and emotional capacities were predictive of supporting conservation in terms of voting and donating to their conservation. Finally, beliefs in animals’ reasoning abilities were predictive of different behavioral expressions of tolerance, and support for their conservation via voting only. Despite the potential injurious capabilities of these species, these findings have important implications for educational and conservation programs to emphasize or modify specific beliefs in order to facilitate particular pro-conservation behaviors for maximum benefits to conservation efforts.